Investigation of the mechanism of poly (ADP-ribose) polymerase (PARP) in elderly mouse myocardial ischemia-reperfusion injury : PARP's role in elderly mouse heart injury - Wang, Xueyuan; Yan, Xiaocan; Xi, Yin; Liu, Jinming (Cellular and Molecular Biology, 2024)
This study investigated the role of Poly (ADP-ribose) Polymerase (PARP) in myocardial ischemia-reperfusion injury (MIRI) in elderly mice. It involves 30 elderly male KM mice divided into three groups: Sham, MIRI, and DPQ, where the MIRI and DPQ groups undergo myocardial ischemia-reperfusion with the DPQ group also receiving DPQ for PARP-1 inhibition. Over three weeks, assessments include histological analysis of myocardial lesions, left ventricular ejection fraction (LVEF) measurements, and evaluations of serum cardiac enzymes and inflammatory markers. This approach aims to understand the protective effects of DPQ in MIRI, focusing on its impact on cardiac health and inflammation via the JAK2/STAT3 pathway. The findings suggest that PARP activation exacerbates cardiac dysfunction and inflammation in MIRI by possibly modulating the JAK2/STAT3 signaling pathway. Inhibition of PARP-1 with DPQ mitigates these effects, as indicated by reduced myocardial lesions and inflammatory infiltration, improved LVEF, and altered levels of inflammatory markers and signaling molecules. However, the differences in STAT3 and p-STAT3 protein expression between the DPQ and MIRI groups were not statistically significant, suggesting that while PARP inhibition affects many aspects of MIRI pathology, its impact on the JAK2/STAT3 pathway may not fully explain the observed benefits. This study contributes to our understanding of the complex mechanisms underlying myocardial ischemia-reperfusion injury, particularly in the context of aging. It highlights the potential of PARP inhibition as a therapeutic strategy to attenuate cardiac dysfunction and inflammation in MIRI, though further research is necessary to fully elucidate the underlying molecular pathways and to explore the clinical relevance of these findings in humans.